(untitled) (Research, Society and Development, 2021)
The aim of this article is to analyze the whole process of changes in the speech of a group of physics teachers who participate in a continued training course. This course belongs to the Regional Education Center (NRE) in the city of Maringá, Brazil. After data analysis, we evidenced three important phases of the behavior of this group of teachers. The first phase is marked by situations of complaints due to the fact of discredit in relation to education and the many challenges faced in daily school life. The second is directed to the wrong methodological practices assumed in the classroom. Finally, the third is a more reflective change of posture. For data analysis, we used the methodologies of Bardin’s theoretical and methodological concepts, based on Content Analysis that delimits some parameters and categories. In this theoretical-methodological framework, whole knowledge can be demonstrated by the learner. In view of such practices, we conclude that it will only be possible to change the complaint speech to reflexive speech when the teacher effectively convinces himself of the need for constant improvements and rescue by his authority often lost in the classroom.